2019
DOI: 10.1177/1078390319886658
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Shiftwork: Designing and Testing a Model for Health Promotion of Iranian Nurses

Abstract: BACKGROUND: Lifestyle is one factor that forms the nurses’ health, particularly those who work in shiftwork schedules. AIMS: The aim of this study was to design and test a model for health promotion of Iranian nurses. In this model, nurses’ lifestyle was considered as the precedent, physical and mental health as the outcomes, and sleep disturbance and chronic fatigue as the mediators. METHODS: A cross-sectional study using structural equation modeling was conducted among 240 shiftworker nurses in Iran. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…One cross-sectional study found a significant positive relationship between nurse fatigue and mental health problems (Bazazan et al, 2019; β = 0.36, p < 0.01). In addition, the study by Mokarami et al (2020) found that nurses’ higher level of chronic fatigue was significantly related to lower mental health status (β = -0.49, p = 0.01). Further, Mokarami et al (2020) found a significant negative association between nurses’ chronic fatigue and their physical health status (β = -0.32, p = 0.01).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…One cross-sectional study found a significant positive relationship between nurse fatigue and mental health problems (Bazazan et al, 2019; β = 0.36, p < 0.01). In addition, the study by Mokarami et al (2020) found that nurses’ higher level of chronic fatigue was significantly related to lower mental health status (β = -0.49, p = 0.01). Further, Mokarami et al (2020) found a significant negative association between nurses’ chronic fatigue and their physical health status (β = -0.32, p = 0.01).…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the study by Mokarami et al (2020) found that nurses’ higher level of chronic fatigue was significantly related to lower mental health status (β = -0.49, p = 0.01). Further, Mokarami et al (2020) found a significant negative association between nurses’ chronic fatigue and their physical health status (β = -0.32, p = 0.01). Another cross-sectional study found that nurses’ musculoskeletal complaints were significantly related to their higher fatigue levels (Mehralizadeh et al, 2017; β = 0.22, p < 0.05).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Shift work changes the awake and sleep time in a 24 h cycle [7] and it has an adverse impact on the amount and quality of sleep, as shift workers cannot avoid concerns about acute sleep loss during night and early morning shifts [2,8]. Adverse effects of poor sleep quality among nurses working shifts include daytime dysfunction, difficulty of recovery after sleep, poor sleep satisfaction, difficulty in sleep maintenance, difficulty with sleep initiation, and difficulty in waking up [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the continued reports of the adverse impact of shift work on nurses' physical and mental health [8], shift work is inevitable for nurses because they must monitor patients, promptly respond to life-threatening situations, and continuously care for patients around the clock.…”
Section: Introductionmentioning
confidence: 99%